2016
DOI: 10.1177/0885328216679761
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of osseointegration by direct coating of rhBMP-2 on target-ion induced plasma sputtering treated SLA surface for dental application

Abstract: Owing to the excellent bioactive properties of recombinant human bone morphogenetic proteins (rhBMPs), dentistry considers them as a fascinating adjuvant alternative for enhancing bone regeneration and bone-to-implant junction in the early implantation stages. However, stable loading and delivery efficiency of rhBMPs on the implant surfaces involve major concerns because of the harsh wearing condition under load during implantation. In this study, to achieve successful rhBMP-2 delivery, a nanoporous surface st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…One of the main reasons for osseointegration-related complications are differences between physico-chemical and structural properties of the injured bone tissue and those of the implant. This has already been confirmed by clinical and experimental studies [ 14 , 15 , 16 ].…”
Section: Introductionsupporting
confidence: 64%
“…One of the main reasons for osseointegration-related complications are differences between physico-chemical and structural properties of the injured bone tissue and those of the implant. This has already been confirmed by clinical and experimental studies [ 14 , 15 , 16 ].…”
Section: Introductionsupporting
confidence: 64%
“…In order to improve the roughness of the surface, many industrial techniques have also been developed to produce a thin coat (sol–gel deposition, sputtering coating techniques, or ion beam-assisted deposition) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The TIPS technique has another important feature in addition to roughening a titanium surface. A previous study showed that TIPS could provide a nanoporous structure on a titanium surface, which could act as a carrier for biomolecules such as recombinant human bone morphogenetic protein-2 (rhBMP-2) 21 . The titanium treated with TIPS showed a significantly higher level of rhBMP-2 in terms of loading capacity and release.…”
Section: Discussionmentioning
confidence: 99%
“…The titanium treated with TIPS showed a significantly higher level of rhBMP-2 in terms of loading capacity and release. This feature might be feasible in compromised osteogenic situations, such as osteoporosis or diabetes 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%